2018
DOI: 10.3390/su10124579
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity of the Chinese Agricultural Futures Market and Its Impact on Futures Price—Based on High-Frequency Data

Abstract: This study examines the price impact of intraday trading activity and daily market liquidity of Chinese agricultural futures by analyzing continuous intraday 15-min and daily trading datasets, respectively. Corn and soybean, the necessity of the nation and people’s survival in China, are taken as case studies. Our main findings are threefold. Firstly, there is evidence of the presence of informed trading through persistent effects of trade size for both purchases and sales. The magnitude of effects and the sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Thus, they find more informative trades in the opening period of the futures market even though traders also have access to the stock market in that period, implying that the derivatives market intrigues informed traders more than the stock market does. Xu and Li (2018) find weaker price impacts during the closing period in the Chinese corn futures market. They argue that investors submit orders aggressively in this period mainly to avoid overnight inventory-holding risk.…”
Section: Intraday Seasonality Analysesmentioning
confidence: 82%
“…Thus, they find more informative trades in the opening period of the futures market even though traders also have access to the stock market in that period, implying that the derivatives market intrigues informed traders more than the stock market does. Xu and Li (2018) find weaker price impacts during the closing period in the Chinese corn futures market. They argue that investors submit orders aggressively in this period mainly to avoid overnight inventory-holding risk.…”
Section: Intraday Seasonality Analysesmentioning
confidence: 82%
“…The remarkable development of China's futures markets also draws scholars' attention to liquidity conditions in Chinese futures markets. However, most studies on Chinese agricultural futures markets use BAS estimators based on daily price data (Liu et al, 2020), daily price and volume data (Zhang & Ding, 2018), or minute‐level trading data (Liu et al, 2021; Xu & Li, 2018). Previous studies on Chinese commodity futures commonly neglect the observed BAS traders encounter directly, which is of great interest to academics and policymakers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of agricultural futures markets in China specifically, Liu et al (2020) assess the market quality of Chinese commodity futures markets from the perspectives of liquidity, efficiency and volatility. Xu and Li (2018) investigate the liquidity of 15 Chinese commodity futures markets under different volatility levels, but they use daily or 5-min trading data instead of BBO data.…”
Section: T Er At U R E R Ev I Ewmentioning
confidence: 99%